2022
DOI: 10.21315/mjms2022.29.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Natural Food for Sarcopenia: A Narrative Review

Abstract: Sarcopenia is a syndrome characterised by progressive loss of skeletal muscle mass and strength. Proper nutrition is essential for management of sarcopenia. Thus, this article aims to review the association between dietary pattern or food groups consisting of natural food and sarcopenia. A literature search was performed using four databases namely PubMed, Scopus, Sage and ScienceDirect. The search terms used were ‘fruits’, ‘vegetables’, ‘egg’, ‘fish’, ‘chicken’, ‘protein food’, ‘ulam’, ‘fresh herbs’, ‘sarcope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(123 reference statements)
0
4
0
2
Order By: Relevance
“…The results from our systematic review suggest that soy consumption may be beneficial in this population for outcomes related to healthy aging, however other reviews on the additional components of the Japanese/Okinawan diet have also reported beneficial effects on these same outcomes [ 80 , 81 , 82 , 83 ]. While our current review cannot comment on the additional components of the Japanese/Okinawan diet, it is of note that dietary patterns are a growing research interest area in the sarcopenia space, and so far research indicates the dietary patterns such as the Japanese/Okinawan diet or the Mediterranean diet are beneficial for healthy aging, compared to Western dietary patterns which appear more harmful [ 73 , 84 , 85 ]. As of 2022, the United States Department of Agriculture concluded there was no significant benefit of any particular dietary pattern for sarcopenia [ 86 ], however this may change as future research moves from specific nutrients such as protein to overall dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our systematic review suggest that soy consumption may be beneficial in this population for outcomes related to healthy aging, however other reviews on the additional components of the Japanese/Okinawan diet have also reported beneficial effects on these same outcomes [ 80 , 81 , 82 , 83 ]. While our current review cannot comment on the additional components of the Japanese/Okinawan diet, it is of note that dietary patterns are a growing research interest area in the sarcopenia space, and so far research indicates the dietary patterns such as the Japanese/Okinawan diet or the Mediterranean diet are beneficial for healthy aging, compared to Western dietary patterns which appear more harmful [ 73 , 84 , 85 ]. As of 2022, the United States Department of Agriculture concluded there was no significant benefit of any particular dietary pattern for sarcopenia [ 86 ], however this may change as future research moves from specific nutrients such as protein to overall dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber administration protects from age-related sarcopenia by improving glucose metabolism, muscle function and lean body mass in adult subjects [283,284]. The underlying mechanism probably involves an increase in the production of short-chain fatty acids by gut microbiota, which are important regulators of skeletal muscle mass, metabolism and function [285], as well as an improvement in glucose homeostasis, with a decrease in insulin resistance and pro-inflammatory cytokine concentration [283,286].…”
Section: Prebiotics and Probioticsmentioning
confidence: 99%
“…Asupan energi yang tidak terpenuhi pada lansia mungkin dipengaruhi oleh malabsorpsi, penggunaan obat anoreksigenik atau gangguan pencernaan. Berdasarkan hasil penelitian telah terjadi penurunan asupan energi sekitar 600 kkal per hari pada perempuan dan 1.330 kkal pada laki-laki diantara usia 20 tahun dan 80 tahun (14). Penelitian Mulla et al (2013) dan Wang et al (2015) menyatakan bahwa asupan energi tinggi berpengaruh terhadap kekuatan otot pada lansia.…”
Section: Pendahuluanunclassified
“…Perubahan fisiologis yang mempengaruhi perubahan kebiasaan makan juga menyebabkan terjadinya kekurangan gizi. Berdasarkan hasil penelitian telah terjadi penurunan asupan energi sekitar 600 kkal per hari pada perempuan dan 1.330 kkal pada laki-laki diantara usia 20 tahun dan 80 tahun, serta meningkatnya risiko penurunan asupan protein pada lansia (14).…”
Section: Pembahasanunclassified